Metode pemberian ASI eksklusif memengaruhi status gizi - Windy Yuniarti; Budiyanti Wiboworini; Yulia Lanti Retno Dewi; Widardo Widardo (Jurnal Gizi Klinik Indonesia, 2020)
Exclusive feeding methods and their effect on nutritional statusBackground: Exclusive feeding could be given by human milk expression or direct breastfeeding methods. Recent studies indicate expressed human milk given by bottle in early infancy could lead to excess weight on the next stage of life. Objective: Determine the differences in nutritional status between exclusively fed infants with direct breastfeeding methods and a combination of breast pumping. Methods: An analytical observational study with the cross-sectional approach, conducted in Puskesmas Jalan Emas, Tangerang Regency, Banten. The subjects consisted of 68 infants from direct breastfeeding (DB) and the combination of breast pumping (KBP) groups, were selected by purposive sampling. The data obtained from the measurement of nutritional status and infants’ feeding history. Results: In WAZ, HAZ, and WHZ in DB were -0.48±0.7; -1.47±1.2; and 0.64±1.19 respectively. In WAZ, HAZ, and WHZ in KBP were 0.06±0.75; -1.66±0.85; and 1.23±1.05 respectively. The T-independent analytical test showed significant score (p) in WAZ, HAZ and WHZ indicators were 0.003; 0.470; and 0.035 respectively. Conclusions: In WAZ and WHZ indicators show significant differences between infants in DB and KBP groups. Meanwhile, in the HAZ indicator, there’s no significant difference between infants in DB and KBP groups.